1981
DOI: 10.1111/j.2042-7158.1981.tb13867.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the intestinal absorption of ergot peptide alkaloids in the rat by micellar solutions of polyoxyethylene-24-cholesteryl ether

Abstract: The incomplete intestinal absorption of hydrogenated ergot peptide alkaloids as measured in bile duct cannulated rats is much increased when the ergot compounds are administered as micellar solutions together with POE‐24‐cholesteryl ether. In vitro diffusion experiments with isolated intestinal mucus show that the ergot peptide alkaloids are strongly retained by the mucus layer. It is suggested that the diffusion of the ergot compounds across the mucus barrier is facilitated by micellar entrapment of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the present study, the absorption enhancing effect of polyoxyethylene (24)-cholesterol-ether (POECE) on the absorption of octreotide and its fluorescent analogue (4nitrobenzo-2-oxa-1,3-diazol-[NBD]-octreotide) was evaluated in an intestinal cell culture model , in animals and in man. Earlier studies showed an absorption enhancing effect of the nonionic detergent POECE on poorly absorbed drugs such as ergot alkaloids (Franz & Vonderscher, 1981) or antibiotics such as streptomycin or cephaloridine (Davis et al, 1970). NBD-octreotide has been demonstrated to have comparable affinity to somatostatin-receptors and similar pharmacodynamic effects after oral administration to the parent peptide (Fricker et al, 1991).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…In the present study, the absorption enhancing effect of polyoxyethylene (24)-cholesterol-ether (POECE) on the absorption of octreotide and its fluorescent analogue (4nitrobenzo-2-oxa-1,3-diazol-[NBD]-octreotide) was evaluated in an intestinal cell culture model , in animals and in man. Earlier studies showed an absorption enhancing effect of the nonionic detergent POECE on poorly absorbed drugs such as ergot alkaloids (Franz & Vonderscher, 1981) or antibiotics such as streptomycin or cephaloridine (Davis et al, 1970). NBD-octreotide has been demonstrated to have comparable affinity to somatostatin-receptors and similar pharmacodynamic effects after oral administration to the parent peptide (Fricker et al, 1991).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Polyoxyethylene cholesteryl ethers with average numbers of oxyethylene units of 8,25,30, and 50 (Chol-En, n = 8, 25,30,50), polyoxyethylene dihydrocholesteryl ethers with average numbers of oxyethylene units ofl5, 30, and 50 (DhChol-En, n = 15, 30, 50) and heptaoxyethylene dodecyl ether (C12E7) of high quality were obtained from Nikko Chemicals Co., Ltd. Egg yolk lecithin (PC) of type V-E, dicetyl phosphate (DCP) and Triton X-100 were purchased from Sigma Chemical Company.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, nonionic surfactants are much used to solubilize biomembranes since these derivatives do not inactivate the membrane-bound proteins [1,2]. Moreover, nonionic surfactants are very popular in the field of pharmaceutics as stimulators of drug absorption [7,8]. But the detailed mechanisms of the above interactions are not sufficiently obvious from the view of chemical structures and properties of nonionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the proportion of ergovaline freed from the plant tissue and absorbed also determines the true physiological dose. A further complication is that ergovaline has been administered in a variety of forms from grazing (Bluett et al 2005;Aiken et al 2011b;Thom et al 2013), feeding whole seed (Gadberry et al 2003;Aiken et al 2009), ground seed (Koontz et al 2012;Koontz et al 2013), or administration of a purified form of ergovaline (Koontz et al 2012;Foote et al 2013). McDowell et al (2013) evaluated whether using ground seed compared with whole seed had an effect on ergovaline-induced vasoconstriction in horses and reported that horses fed ground seed had greater reductions in artery lumen diameter, circumference and area than did horses fed whole seed.…”
Section: Ergovaline Deliverymentioning
confidence: 99%
“…This last route would bypass a first-pass detoxification of ergovaline by the liver and, instead, direct the absorbed ergovaline to the heart for systemic distribution via arterial blood supply before detoxification by the liver. Franz and Vonderscher (1981) reported that intestinal absorption of ergopeptine alkaloids in the rat was enhanced when the alkaloids were administered in micellar solutions. As lipids are commonly absorbed from the intestinal lumen in the form of micelles through a lacteal leading to the lymphatic system and given the lipophilic nature of ergovaline and the other ergopeptine alkaloids, the lymphatic route of intestinal absorption is likely in ruminants as well.…”
Section: Ergovaline Absorptionmentioning
confidence: 99%